1997
DOI: 10.1149/1.1837600
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Plasma Etch Systems Using Ordinary Least Squares, Recurrent Neural Network, and Projection to Latent Structure Models

Abstract: In microelectronics manufacturing, control strategies for plasma etch systems have been limited to traditional statistical process control and recipe control techniques. The lack of in situ real-time measurements of process performance and appropriate models has hindered the introduction of feedback control systems. This paper focuses on empirical model building for advanced process control using two real-time diagnostic sensors for measurement of the reactor state. Laser interferometry for measurement of etch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…[24][25][26][27] Since data generated in plasma etch equipment has collinearity, measurement noise and huge amount of sensor variables, PLSR works well in plasma etching. 13,[28][29][30] PLSR can avoid collinearity problems among variables in such a way to utilize orthogonal latent variables. The orthogonal latent variables are result of re-arrangement in such a way to have maximum correlation between input and output variables.…”
Section: Partial Least Squares Regressionmentioning
confidence: 99%
“…[24][25][26][27] Since data generated in plasma etch equipment has collinearity, measurement noise and huge amount of sensor variables, PLSR works well in plasma etching. 13,[28][29][30] PLSR can avoid collinearity problems among variables in such a way to utilize orthogonal latent variables. The orthogonal latent variables are result of re-arrangement in such a way to have maximum correlation between input and output variables.…”
Section: Partial Least Squares Regressionmentioning
confidence: 99%
“…The improved understanding of plasma properties has led to the development of accurate mathematical models for various plasma etching processes which can be used to compute reactor con"gurations that reduce the etching nonuniformity (e.g. Park & Economou, 1990;Park & Economou, 1991;Bushman, Edgar, & Trachtenberg, 1997;Venkatesan, Trachtenberg, & Edgar, 1987). Such studies have revealed that the use of a showerhead arrangement to introduce the precursor gas into the reaction chamber, signi"cantly reduces the radial etching nonuniformity.…”
Section: Introductionmentioning
confidence: 99%
“…We offer a software implementation based on the latter approach using a cascade correlation neural network for the critical prediction algorithm. While other such neural-network approaches to quality metric prediction for semiconductor tools have been reported [3], [14]- [16], we offer a predictive model that accounts for both continuously modulated variables as well as time-dependent maintenance variables, such as parts cleaning, and replacement. This mixed model was developed to serve as a real time aid for the tool operator and engineer, and incorporates all the actions that are considered for maintenance of process control on a daily basis.…”
Section: Introductionmentioning
confidence: 99%